Effect of Ownership Structure on Corporate Diversification of Listed Firms in Kenya - Peninah Jepkogei Tanui; Josephat Cheboi Yegon; Ronald Bonuke (SEISENSE Journal of Management)
Purpose - This paper aimed to examine the moderating role of capital structure in the relationship between institutional and foreign ownerships on corporate diversification of listed firms at the Nairobi Securities Exchange, Kenya.